Pengaruh Posisi Pemangkasan Daun Jagung Dalam Sistem Tumpang Sari Terhadap Pertumbuhan dan Hasil Kedelai - Mapegau Mapegau; Islah Hayati; Addion Nizori; Ardiyaningsih Puji Lestari; Marlina Marlina (Universitas Batanghari, 2022)
This study aims to determine the effect of corn leaf pruning on soybean growth and yield in an intercropping system. This research was carried out on farmers' land in Simpang Village, Berbak District, Tanjung Jabung Timur Regency from July - October 2020. This research was carried out using a Randomized Block Design (RBD) with 5 replications. Pruning treatments based on the position of the leaves on the stem were : without pruning (control/p0), pruning 3 leaves at a position near the soil surface (p1), pruning 3 leaves at a position below the cob (p2), and pruning 3 leaves at a position above the cob (p3). The variables observed included soybean plant height (cm), number of pods per plant, number of filled pods per plant, weight of 100 dry seeds (g), and soybean dry seed yield. The results showed that the highest soybean plant height was obtained without pruning and pruning 3 corn leaves near the soil surface, but produced the lowest number of pods per plant, number of filled pods, and the lowest soybean dry seed yield. The number of pods per plant, the number of containing per plant, and the highest soybean dry seed yield were obtained at pruning of 3 leaves under the cob and 3 leaves of corn above the cob. In corn, the highest yield was obtained by pruning 3 leaves below the cob and 3 leaves above the cob. The diversity of soybean dry seed yields in this study was determined jointly by the diversity of the number of pods per plant, the number of filled pods per plant, and the weight of 100 dry seeds. Partially, only the number of pods contained per plant and the weight of 100 dry seeds significantly played a role in determining the amount of dry soybean yield, while the number of pods per plant had no significant role in determining the diversity of dry seed yields. Land use with corn and soybean intercropping system can increase land productivity so that it is more efficient with LER value > 1 in all positions of corn leaf pruning. Keywords: pruning, intercropping corn, soybean